2008
DOI: 10.2137/145960610791542334
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization and yield formation of potato during a short growing period

Abstract: The effects various rates of nitrogen application on accumulation of dry matter and nitrogen in potato (Solanum tuberosum L.) were studied during a short growing period of 140-180 days, at MTT Agrifood Research Finland in 2000-2001. The treatments were 0, 60 and 120 kg N ha -1 and the potato cultivars tested were Van Gogh and Nicola. Four successive harvests were made during the course of the experiment to monitor changes in the accumulation of dry matter and nitrogen over the season. Applications of nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…With more nitrogen, there is an increase in the number of leaves (photosynthetically active) as well as in the rate of leaf per plant due to more branching, particularly at the upper portion of the plant (Oliveira, 2000). Vos and Biemond (1992) and Mustonen et al (2010) showed that different nitrogen treatments resulted in plants that differed considerably in final dry weight and tuber yield. Generally Indian soil have been reported to be low in nitrogen, hence its supply through fertilizers may play an important role in crop production but indiscriminate use of them is hazardous to crop as well as for environment (Meena et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With more nitrogen, there is an increase in the number of leaves (photosynthetically active) as well as in the rate of leaf per plant due to more branching, particularly at the upper portion of the plant (Oliveira, 2000). Vos and Biemond (1992) and Mustonen et al (2010) showed that different nitrogen treatments resulted in plants that differed considerably in final dry weight and tuber yield. Generally Indian soil have been reported to be low in nitrogen, hence its supply through fertilizers may play an important role in crop production but indiscriminate use of them is hazardous to crop as well as for environment (Meena et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the lowest dry matter accumulation in the potato shoots with N0 and MN may be due to low availability of N for the tissues of this part of potato plants, causing premature defoliation under low doses of this nutrient (Goffart et al, 2008). The lowest dry mass in the shoots of potato after 65 DAP is due to early senescence of its leaves at the end of the cycle when photoassimilates are translocated to the tubers (Mustonen et al, 2010).…”
Section: Dry Matter In Shoots Tubers and Total Potatomentioning
confidence: 99%
“…Os fotoassimilados, produzidos pela atividade fotossintéti-ca, são direcionados para o crescimento, sendo a partição para os tubérculos um dos fatores determinantes da produtividade da cultura da batata. A produção de matéria seca pela planta e a partição para os tubérculos são influenciados por diversos fatores, tais como interceptação luminosa (Harris, 1992), alta temperatura, por aumentar a senescência foliar e reduzir a capacidade fotossintética (Timlin et al, 2006), fotoperíodo (Haverkort e Verhagen, 2008), cultivar (Zebarth, et al, 2006;Geremew et al, 2007), época de cultivo (Mustonen et al, 2010), manejo da cultura (Geremew et al, 2007) e fertilização nitrogenada (Zebarth e Rosen, 2007). Na batata, há produção de matéria seca na parte aérea e nos tubérculos, que acumulam a maior quantidade, atingindo de 68% a 84% da biomassa total produzida pela planta (Sharifi et al, 2005;Nunes et al, 2006).…”
unclassified